Constitutional orphan gender equality and the Nineteenth Amendment - Monopoli, Paula A. 1958- (Oxford University Press, 2020)
On August 26, 1920, these words became part of the United States Constitution as its Nineteenth Amendment. The requisite thirty- six states had ratified the amendment in the year since its enactment by Congress on June 4, 1919. A revolution in women's rights, spanning over seventy years, came to a quiet conclusion as Secretary of State Bainbridge Colby signed the measure into law in the privacy of his home at eight o'clock in the morning.1 None of the prominent suffrage leaders of the day, including the National American Woman Suffrage Association (NAWSA) president, Carrie Chapman Catt; or the National Woman's Party (NWP) chair, Alice Paul, were at the signing.2 Catt was later invited to go to the State Department to see the proclamation, but no similar invitation was extended to the more militant Paul. Paul had been a thorn in the side of President Woodrow Wilson, with her White House picketing and willingness to be imprisoned for the vote.3 Ratification was followed by ten years of litigation- most of it in state courts- during which the meaning and scope of the Nineteenth Amendment was contested. In its most literal sense, the Nineteenth Amendment did not confer a "right" to vote per se. Rather, it simply prohibited the states or the federal government from using sex as a criterion for voter eligibility.4 In other words, its ratification meant that state and federal impediments to voting based on sex were now unconstitutional. It did not mean that all women in the United States could vote.5 As a matter of law, the Nineteenth Amendment meant that states could not prevent African American women from voting based solely on their sex. Yet vast numbers of African American women were prevented from voting in the November 1920 presidential election that followed on the heels of ratification.6 They faced the same impediments- poll taxes, literacy tests, grandfather clauses, and physical intimidation- used to prevent their male counterparts from voting after ratification of the Fourteenth and Fifteenth Amendments.7 Those amendments conferred citizenship on previously enslaved persons and barred state or federal restrictions on voting based on race, color, and previous condition of servitude"--